(untitled) (Acta Polytechnica CTU Proceedings, 2015)
Mass transfer and accretion are very important to understand the evolution and observational properties of cataclysmic variables (CVs). Due to the lack of an accretion disk, eclipsing profiles of polars are the best source to study the character of mass transfer in CVs. By analyzing long-term photometric variations in the eclipsing polar HU Aqr, the property of mass transfer and accretion are investigated. The correlation between the brightness state change and the variation of the ingress profile suggests that both the accretion hot spot and the accretion stream are produced instantaneously. The observations clearly show that it is the variation of mass transfer causing the brightness state changes that is a direct evidence of variable mass transfer in a CV. It is shown that it is the local dark-spot activity near the L1 point to cause the change of the mass transfer rather than the activity cycles of the cool secondary star. Our results suggest that the evolution of CVs is more complex than that predicted by the standard model and we should consider the effect of variable mass accretion in nova and dwarf nova outbursts.